A word of caution about biological inference – Revisiting cysteine covalent state predictions. Issue 1 (12th March 2014) - Tüdős, Éva; Mészáros, Bálint; Fiser, András; Simon, István
Abstract : The success of methods for predicting the redox state of cysteine residues from the sequence environment seemed to validate the basic assumption that this state is mainly determined locally. However, the accuracy of predictions on randomized sequences or of non‐cysteine residues remained high, suggesting that these predictions rather capture global features of proteins such as subcellular localization, which depends on composition. This illustrates that even high prediction accuracy is insufficient to validate implicit assumptions about a biological phenomenon. Correctly identifying the relevant underlying biochemical reasons for the success of a method is essential to gain proper biological insights and develop more accurate and novel bioinformatics tools. Abstract : High prediction accuracy is often believed to validate implicit biological assumptions. Cys redox state predictions assume a local sequence environmental effect. Removing local sequence signals did not reduce prediction accuracy. Cys redox state predictions apparently correlate with subcellular localization. Subcellular localization depends on global sequence composition.